Leukocyte Immunoglobulin-Like Receptors (LILRs) on Human Neutrophils: Modulators of Infection and Immunity - Lewis Marffy, Alexander L.; McCarthy, Alex J. (Frontiers in Immunology, 2020)
Neutrophils have a crucial role in defence against microbes. Immune receptors allow neutrophils to sense their environment, with many receptors functioning to recognise signs of infection and to promote antimicrobial effector functions. However, the neutrophil response must be tightly regulated to prevent excessive inflammation and tissue damage, and regulation is achieved by expression of inhibitory receptors that can raise activation thresholds. The leukocyte immunoglobulin-like receptor (LILR) family contain activating and inhibitory members that can up- or down-regulate immune cell activity. New ligands and functions for LILR continue to emerge. Understanding the role of LILR in neutrophil biology is of general interest as they can activate and suppress antimicrobial responses of neutrophils and because several human pathogens exploit these receptors for immune evasion. This review focuses on the role of LILR in neutrophil biology. We focus on the current knowledge of LILR expression on neutrophils, the known functions of LILR on neutrophils, and how these receptors may contribute to shaping neutrophil responses during infection.